Hubungan Pengetahuan Ibu Tentang Pola Asupan Nutrisi Dengan Kenaikan Berat Badan Bayi 6-12 Bulan Di Puskesmas Keritang Hulu Kecamatan Kemuning Tahun 2023 - Irawati Pasaribu; Ika Erniati; Insyirah Br Harahap; Ira Yani Estuti; Irawati Manurung; Debi Novita Siregar (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Impaired growth and development can occur if nutrition in infancy and children is not fulfilled and is not treated early. Fulfillment of nutritional needs in infants, especially in infants aged 6-12 months where at this time babies are introduced to food, or termed MP-ASI, you should pay attention to several things such as the nutritional content of the ingredients used, administration according to nutritional needs, can be well received by the baby's digestion, preferably produced from local ingredients and is dense in nutrition. Knowledge about nutritional intake patterns is needed by every mother, so that the baby's nutritional needs can be optimal. The purpose of this study was to determine the relationship between maternal knowledge about nutritional intake patterns and weight gain for babies aged 6-12 months at the Keritang Hulu Health Center, Kemuning District. The results of the study showed that 29 mothers (72.5%) had good nutritional patterns and 29 mothers (100%) had weight gain. However, there were 11 mothers who had poor nutritional patterns (27.5%) and all of these mothers' babies did not experience weight gain (100%). the results of the statistical chi-square test that has been carried out show a Pvalue (> 0.05), namely 0.000. The research hypothesis states that there is a relationship between maternal knowledge about nutritional intake patterns and weight gain for infants aged 6-12 months at the Keritang Hulu Health Center, Kemuning District, in 2023. Conclusion Sufficient knowledge about nutritional patterns will have an impact on infant weight gain. It is hoped that all mothers who have babies will be able to find more information about how good nutritional patterns are for babies aged 6-12 months so that they have an impact on optimal baby growth and development according to the baby's age.